2000
DOI: 10.1016/s0960-9822(00)00448-6
|View full text |Cite
|
Sign up to set email alerts
|

Active demethylation of the paternal genome in the mouse zygote

Abstract: DNA methylation is essential for the control of a number of biological mechanisms in mammals [1]. Mammalian development is accompanied by two major waves of genome-wide demethylation and remethylation: one during germ-cell development and the other after fertilisation [2] [3] [4] [5] [6] [7]. Most previous studies have suggested that the genome-wide demethylation observed after fertilisation occurs passively, that is, by the lack of maintenance methylation following DNA replication and cell division [6] [7], a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
594
2
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 904 publications
(638 citation statements)
references
References 23 publications
25
594
2
7
Order By: Relevance
“…During the initial 0-5 h.p.f., the parental genomes exhibit dramatic epigenetic differences. The paternal genome undergoes marked demethylation while the maternal genome, which contains most of the methylation marks associated with imprints, undergoes further de novo methylation 11,12,47 . Species where imprinting is unknown do not show such differential methylation of parental genomes during early development.…”
Section: Genomic Reprogramming In the Zygotementioning
confidence: 99%
See 2 more Smart Citations
“…During the initial 0-5 h.p.f., the parental genomes exhibit dramatic epigenetic differences. The paternal genome undergoes marked demethylation while the maternal genome, which contains most of the methylation marks associated with imprints, undergoes further de novo methylation 11,12,47 . Species where imprinting is unknown do not show such differential methylation of parental genomes during early development.…”
Section: Genomic Reprogramming In the Zygotementioning
confidence: 99%
“…Loss of function of either of the two genes results in the loss of germ cell lineage in worms. Genome-wide demethylation is also observed in PGCs and in the paternal genome in the zygote 11,12,56 , although it is important to note that whereas the imprints are erased in PGCs, this is not the case during embryonic development.…”
Section: Genomic Reprogramming In the Zygotementioning
confidence: 99%
See 1 more Smart Citation
“…14,15 This important pathway for active DNA demethylation has been thought to be involved in a number of prominent biological processes. 5,6,10,11 Early and recent studies suggested that active and replication-independent DNA demethylation might be a rapid process. 10,11 The radically altered methylation, as observed in replication-independent demethylation of the paternal genome in zygotes, may complete within hours.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pre-existing 5-methylcytosines (5-MeCs) of the incoming sperm genome are removed in the oocyte cytoplasm in mice Oswald et al, 2000;Santos et al, 2002). Active demethylation of paternally derived genome has been asserted to occur by showing asymmetric methylation states between the male and the female pronuclei in rat, cow, and pig zygotes .…”
Section: Introductionmentioning
confidence: 99%